2016
DOI: 10.1002/mus.25091
|View full text |Cite
|
Sign up to set email alerts
|

Creatine supplementation does not alter neuromuscular recovery after eccentric exercise

Abstract: CR supplementation before and during recovery from ECC had no effect on strength, voluntary activation, or indicators of muscle damage. Muscle Nerve 54: 487-495, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…These acute physiological responses were similar between groups, indicating that the standard creatine loading protocol used exhibited a limited potential to attenuate markers of muscle damage and soreness following the bout of resistance exercise inducing muscle damage. Similar findings have also been reported in which creatine supplementation did not appear to attenuate markers of muscle damage, soreness, strength deficits, or fatigue following exercise [121,[126][127][128][129].…”
Section: Loss Of Force Production Muscle Damage Soreness and Inflammationsupporting
confidence: 85%
“…These acute physiological responses were similar between groups, indicating that the standard creatine loading protocol used exhibited a limited potential to attenuate markers of muscle damage and soreness following the bout of resistance exercise inducing muscle damage. Similar findings have also been reported in which creatine supplementation did not appear to attenuate markers of muscle damage, soreness, strength deficits, or fatigue following exercise [121,[126][127][128][129].…”
Section: Loss Of Force Production Muscle Damage Soreness and Inflammationsupporting
confidence: 85%
“…Several types of inflammatory biomarkers were reported, including IL-6 (two studies), TNFα (two studies), CRP (one study), interferon-α (one study), and IL-1β (one study). Similarly, [46] 1 1 1 0 1 1 1 1 1 0 1 1 1 1 1 13/16 Excellent Bassit et al [47] 1 1 1 0 1 1 1 1 1 0 1 1 1 1 1 13/16 Excellent Basta et al [48] 1 0 1 0 1 0 0 0 0 0 1 1 1 1 1 8/16 Fair Boychuk et al [49] 1 2 1 0 1 1 1 1 1 0 1 1 1 1 1 14/16 Good Brose et al [50] 1 0 1 0 0 0 0 1 1 1 1 1 1 1 1 10/16 Fair Cooke et al [26] 1 2 1 0 1 1 1 1 1 0 1 1 1 1 1 14/16 Good Fernandez-Landa et al [30] 1 1 1 1 1 1 0 1 1 0 1 1 1 1 1 13/16 Good Hayward et al [33] 1 1 1 0 1 1 1 0 0 0 1 1 1 1 1 11/16 Good Kaviani et al [31] 1 1 1 0 1 1 1 1 1 0 0 1 1 1 1 12/16 Good Machado et al [51] 1 1 1 1 1 0 0 1 1 0 1 1 1 1 1 12/16 Good McKinnon et al [34] 1 1 1 1 1 0 1 1 1 0 1 1 1 1 1 13/16 Good Mirzaei et al [52] 1 1 1 0 1 1 0 1 1 0 1 1 1 1 1 12/16 Good Percario et al [32] 1 1 1 0 1 1 0 1 1 1 1 1 1 1 1 13/16 Excellent Rahimi [53] 1 1 1 0 1 1 1 1 1 0 0 1 1 1 1 12/16 Good Rawson et al [35] 1 0 1 0 1 1 1 1 1 0 1 1 1 1 1 12/16 Good Rawson et al [37] 1 1 1 0 1 1 1 1 1 0 1 1 1 1 1 13/16 Good Santana et al [54] 1 1 1 0 1 0 1 1 1 0 1 1 1 1 1 12/16 Good Santi et al [55] 1 1 1 0 1 1 0 1 1 1 1 1 1 1 1 13/16 Good Santos et al [56] 1 2 1 0 1 1 1 1 1 1 1 1 1 1 1 15/16 Excellent Taylor et al [36] 1 2 1 0 0 0 1 1 1 0 1 1 1 1 1 12/16 Good Veggiv [27] 1 1 1 0 1 1 1 0 0 0 1 1 1 1 1 11/16 Good Wang et al [28] 1 2 1 0 1 1 0 1 1 0 1 1 1 1 1 13/16 Good various oxidative stress markers were reported, including thiobarbituric acid reactive substances (TBARS; two studies), 8-Oxo-2′-deoxyguanosine (8-OHdG; two studies), glutamic oxaloacetic transaminase (one study), glutathione peroxidase (one study), malondialdehyde (one study), and 8-iso-prostaglandin F2α (one study).…”
Section: Methodological Descriptionsmentioning
confidence: 99%
“…In contrast, several other studies have shown no positive effects of similar Cr supplementation protocols on markers of muscle damage or physical recovery following resistance-based exercise [ 141 , 142 , 143 ]. Interestingly, Rosene [ 144 ] found no effect of Cr supplementation on post-exercise recovery when consumed in a dose of 20 g/day for 7 days pre-exercise.…”
Section: Proteins and Amino Acidsmentioning
confidence: 96%